2020
DOI: 10.21580/vjv9i14847
|View full text |Cite
|
Sign up to set email alerts
|

Blogging in Extensive Reading: Students’ Voice in Blended Learning Classroom

Abstract: <p>The use of a blog as a platform for extensive reading becomes valuable since it provides the possibility of readership and opportunity for interaction and collaboration. As the online journal facilitating users to display information in chronological order and connected to the Internet, the blog also can help students to get a wide variety of reading materials, which should be conducted in extensive reading activities. However, the use of a blog in this study is integrated with the process of learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Since online learning mostly relies on the internet connection, internet signal becomes vital for the continuous implementation of online learning (Derakhshan & Hasanabbasi, 2015;Fatimah et al, 2020). Considering that Indonesia is formed by thousands of islands with various geographical and economic conditions, it is not easy to expect equal internet access throughout Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Since online learning mostly relies on the internet connection, internet signal becomes vital for the continuous implementation of online learning (Derakhshan & Hasanabbasi, 2015;Fatimah et al, 2020). Considering that Indonesia is formed by thousands of islands with various geographical and economic conditions, it is not easy to expect equal internet access throughout Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…application through the collections of graded reading materials (Ermerawati, 2019) that can be selected by the students themselves (Prihartono et al, 2021). Furthermore, the digital extensive reading program was also implemented through blogging or through the use of a blog as a platform for extensive reading (Fatimah et al, 2020). In addition, the digital extensive reading program could also be implemented by using Mobile-Assisted through the 0 1 2 3 Resources collections of e-books for extensive reading (Ni'mah & Umamah, 2020).…”
Section: Figure: 1 the Implementation Of Digital Extensive Reading In...mentioning
confidence: 99%
“…To support the implementation of digital extensive reading, blogging can be used to facilitate EFL students' extensive reading. Fatimah et al (2020) found out that blogs could be utilized as a tool for EFL students to look for various reading materials that could be adjusted according to their level of language ability and interest (Fatimah et al, 2020). Furthermore, EFL teachers could also include links that contain reading resources as references of the materials, so that EFL students could develop their digital extensive reading activities through blogging (Fatimah et al, 2020).…”
Section: Digital Extensive Reading Through Bloggingmentioning
confidence: 99%
“…Ghanizadeh et al, (2015) argued that technology was used in almost all areas of language learning. It offers a powerful way of enabling the student to be fully engaged in their language learning activities and become the new ways of presenting or representing information to the students (Cacheiro-Gonzalez, 2019;Fatimah et al, 2020;Fatimah & Santiana, 2017;Siti Fatimah & Sulastri, 2021). To manage this, higher education institutions have started to use Learning Management Systems (LMS) for the organization of courses.…”
Section: Introductionmentioning
confidence: 99%